Inside Cover: Antibody–Drug Conjugates with Pyrrole‐Based KSP Inhibitors as the Payload Class (Angew. Chem. Int. Ed. 46/2018). Issue 46 (12th October 2018) - Lerchen, Hans‐Georg; Wittrock, Sven; Stelte‐Ludwig, Beatrix; Sommer, Anette; Berndt, Sandra; Griebenow, Nils; Rebstock, Anne‐Sophie; Johannes, Sarah; Cancho‐Grande, Yolanda; Mahlert, Christoph; Greven, Simone; Terjung, Carsten
Abstract : Targeted killing of tumor cells with antibody–drug conjugates (ADCs) utilizing kinesin spindle protein inhibitor payloads is described in the Communication by Lerchen et al. onpage 15243 ff. Upon binding of the armed antibody to tumor‐specific antigens, the ADC is internalized into lysosomal compartments, where the active metabolite is released. Subsequent inhibition of KSP, an ATP‐dependent motor protein involved in the generation of bipolar spindles, finally leads to apoptosis. (Artwork by The New Atlantic, Cologne.)